2000
DOI: 10.1159/000016043
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cerebral Circulation Time by Contrast-Enhanced Doppler Sonography

Abstract: We present a new, non-invasive ultrasound method for the measurement of cerebral circulation time. After injection of a galactose-based echo-contrast agent (Levovist) into an antecubital vein, cerebral circulation time is measured as the interval between the beginning of a stable signal enhancement of at least 5 dB in the internal carotid artery and in the ipsilateral internal jugular vein. Both vessels are insonated simultaneously at the mandibular angle using a single 2-MHz range-gated transducer. For this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…The presented values of global CCT, obtained in our group of normal individuals, are within the range of previously published data [2, 4, 5, 14]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The presented values of global CCT, obtained in our group of normal individuals, are within the range of previously published data [2, 4, 5, 14]. …”
Section: Discussionsupporting
confidence: 90%
“…Up to now only few studies are published, trying to establish and apply ultrasound CCT assessment in an experimental or clinical setting [1, 2, 12, 13, 14, 15, 16, 17]. A regional CCT, assessed between the posterior cerebral artery and the vein of Galen by transcranial colour-coded duplex sonography (TCCS) was shown to be prolonged in patients with CADASIL and vascular dementia [12, 13, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we introduced a novel method of measuring cerebral circulation times using 320-detector row 4D CTA. The CCT we calculated as the time interval between the arrival of a bolus of contrast medium at the skull base level of the ICA and the arrival of the bolus in the jugular bulb was 5.8 ± 1.4 s, which is in line with previous studies that derived CCT values by means of DSA and contrastenhanced ultrasound [6,7,9]. However, DSA requires invasive arterial catheterization with its well-known inherent risks, stroke being the most feared [10,11].…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, we analyzed the cerebral perfusion time in IIH patients as compared to controls using a noninvasive dynamic duplex sonography technique. Cerebral perfusion can be measured using color-coded duplex sonography either transcranially [14,15] or extracranially [16]. Compared to controls, Liebetrau et al [15] observed prolonged CTT in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy.…”
Section: Discussionmentioning
confidence: 99%